Oxygen isotope zoning in garnet from Sør Rondane Mountains, East Antarctica - Fumiko, Higashino; Daniela, Rubatto; Tetsuo, Kawakami; Anne-Sophie, Bouvier (2017)
第8回極域科学シンポジウム/個別セッション：[OG] 極域地圏 12月6日（水）国立極地研究所 3階セミナー室 The Eighth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences Wed. 6 Dec./3F Seminar room, National Institute of Polar Research conference object